On the capabilities of the SWOT satellite to monitor the lake level change over the Third Pole. (17th March 2023) - Xiong, Jinghua; Jiang, Liguang; Qiu, Yuanlin; Wongchuig, Sly; Abhishek; Guo, Shenglian; Chen, Jie
Abstract: The lake level dynamics of the Qinghai–Tibetan Plateau (QTP, also called the 'Third Pole') are a crucial indicator of climate change and human activities; however, they remain poorly measured due to extremely high elevation and cold climate. The existing satellite altimeters also suffer from relatively coarse temporal resolution or low spatial coverage, preventing effective monitoring of lake level change at such a large spatial scale. The recently launched surface water and ocean topography (SWOT) mission is expected to greatly enhance the current lake level monitoring capabilities. However, a systematic evaluation is still lacking in the region. To elucidate this potential, here, we generated SWOT-like lake products for 38 major lakes (>150 km 2 ) over the QTP during 2000–2018 using a large-scale SWOT hydrology simulator with the input of satellite altimetry and water mask databases. The comparative assessments between the satellite altimetry data and SWOT simulations using various statistical metrics and decomposed time series components demonstrate that SWOT can successfully monitor both short-term dynamics and long-term trends. Extended experiments to derive SWOT-like data of 783 lakes (>1 km 2 ) based on the synthetic lake level series present the spatial pattern of SWOT performance that tends to improve with the increasing lake area. Our findings provide comprehensive inferences and confidence for lake level monitoring in the Third Pole in the early period of the SWOT satellite.